Comparison of survival and post-operation outcomes for minimally invasive versus open hepatectomy in hepatocellular carcinoma: A systematic review and meta-analysis of case-matched studies - Fu, Bing; Zhang, Jin-Rui; Han, Pin-Sheng; Zhang, Ya-Min (Frontiers in Oncology, 2022)
Background With the rapid development of minimally invasive techniques and instruments, more and more patients begin to accept minimally invasive surgery. Minimally invasive hepatectomy (MIH) has obvious advantages in terms of surgical incision, but there is still no strong evidence of its long-term survival effect. The primary objective of this study was to compare long-term survival outcomes between MIH and Open hepatectomy (OH) in hepatocellular carcinoma based on high-quality case-control studies. Methods The study on the comparison of MIH (including RH or LH) and OH in the treatment of HCC from the date of establishment to June 1, 2022 was searched through PubMed, Web of Science, Embase and Cochrane Library databases. The main results were long-term overall and disease-free survival and short-term postoperative effect; All studies were conducted according to PRISMA guidelines, and meta-analysis of random effect models was adopted. Results 43 articles included 6673 patients. In these studies, the data from 44 studies need to be extracted and pooled in the meta-analysis. Our results showed that compared with OH group, OS (HR 1.17; 95%CI 1.02, 1.35; P=0.02) and DFS (HR 1.15; 95%CI 1.05, 1.26; P=0.002) in MIH group were slightly lower than those in OH group. The operation time (Z=2.14, P=0.03, MD8.01, 95% CI: 2.60–13.42) was longer than OH group. In terms of length of hospital stay (Z=10.76, p<0.00001, MD -4.0, 95% CI: -4.72 to -3.27), intraoperative blood loss, blood transfusion rate, postoperative complications, major morbidity and mortality, the MIH group was significantly better than the OH group. The meta-analysis showed no significant difference in terms of major hepatectomy, anatomical resection , satellite nodules, microvascular invasion, R0 resection and recurrence . Conclusion: This study is the first to compare the clinical efficacy of MIH and OH in the treatment of HCC based on a high-quality propensity score matching study. The results show that in terms of long-term survival outcomes (OS and DFS), although the gap between MIH and OH is not obvious, OH was better than MIH on the whole. However, in terms of short-term postoperative outcomes (post-operation outcomes), MIH was slightly better than OH.